Retrospective Observational Study of Daytime Add-On Administration of Zopiclone to Difficult-to-Treat Psychiatric Inpatients With Unpredictable Aggressive Behavior, With or Without EEG Dysrhythmia - Ceccherini-Nelli, Alfonso; Bucuci, Elena; Burback, Lisa; Li, Daniel; Alikouzehgaran, Maryam; Latif, Zahid; Morin, Kevin; Ganapathy, Karthikeyan; Salsali, Manhaz; Abdullah, Ubaid; Westwood, Wanda; Orris, Janice; et al. (Frontiers in Psychiatry, 2021)
Managing violent behavior is a particularly challenging aspect of hospital psychiatric care. Available pharmacological interventions are often unsatisfactory. Aim: To assess the effectiveness and safety of daytime zopiclone add-on administration in violent and difficult-to-treat psychiatric inpatients. Methods: chart review of inpatients treated with daytime zopiclone, between 2014 and 2018, with up to 12 weeks follow-up. Effectiveness was retrospectively assessed with the Clinical Global Impression rating scale (CGI) and the frequency and severity of aggressive incidents recorded with the Staff Observation Aggression Scale-Revised (SOAS-R). Results: Forty-five (30 male, 15 female) cases, 18-69 years age range, average (SD) baseline CGI-S score of 5.4 (1.0), and a variety of diagnoses. Sixty-nine percent showed CGI-S improvement of any degree. For patients with at least one aggressive incident within 7 days prior to initiation of zopiclone (N=22), average (SD) SOAS-R-Severity LOCF to baseline change was -3.5 (2.7) P<0.0001. Most patients reported no side effects; 24% reported one or more side effects, and 11% discontinued zopiclone due to sedation (4), insomnia (1), slurred speech (1). No SAEs were recorded. Zopiclone maximum daily dose correlated with CGI-S baseline-to-LOCF change (rho = -0.5, P=0.0003). The ROC AUC of zopiclone maximum daily dose and improvement on CGI-S was 0.84 (95% CI 0.70 to 0.93, P<0.0001). The ROC AUC of zopiclone maximum daily dose and SOAS-R-N improvement was 0.80 (95% CI 0.58 to 0.92; P=0.0008) and maximum Youden's index value was achieved at a dose of >30 mg. Conclusions: Zopiclone doses >30 mg daily achieved the best anti-aggressive effect.